THE IMPLEMENTATION OF GALLERY WALK LEARNING MODEL TO IMPROVE VERBAL COMUNICATING SKILL OF PERFORMANCE RESULT THRU THEMATIC LEARNING - Candrika Sekar Pertiwi; Lies Lestari; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2018)
The purpose of this research is to improve verbal communicating skill of performance result thru thematic learning in fourth grade students of SD Negeri in Sukoharjo Regency in the academic year of 2017/2018. The method used in this research is Classroom Action Research (CAR) was conducted in two cycles. Each cycle consist of four steps i.e. planning, action, observation, and reflection. The research data was collected by using several techniques such as observation, interview, test, and documentation. The data validity test was using triangulation technique and content validity. The model interactive of analyzing was used on data analyze technique. The assessment result showed both students’ verbal communicating skill and teacher’s performance increased continously. According to the result of this research, implemented Gallery Walk learning model can improve verbal communicating skilll of performance result thru thematic learning for 4th grade students of SD Negeri in Sukoharjo Regency in the academic year of 2017/ 2018.